2011
DOI: 10.1901/jaba.2011.44-357
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Response Variability of Mand Frames With Script Training and Extinction

Abstract: We examined the effects of script training and extinction on response variability of mand frames used by children with autism. Results demonstrated that extinction following script training was effective for increasing variability for 2 of the 3 participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
83
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 50 publications
(88 citation statements)
references
References 7 publications
(7 reference statements)
5
83
0
Order By: Relevance
“…Due to the success of extinction promoting mand variability in previous studies (e.g., Betz et al, 2011) and the results of Sellers (2011) that suggested that antecedent and consequence manipulations may promote mand variability, extinction served as a viable option for increasing response variability. In this condition, they reinforced the first response of each complete mand frame, but put subsequent responses of that mand frame on extinction for the remainder of the phase.…”
Section: Responding Variably Under the Context Of Requestingmentioning
confidence: 99%
See 4 more Smart Citations
“…Due to the success of extinction promoting mand variability in previous studies (e.g., Betz et al, 2011) and the results of Sellers (2011) that suggested that antecedent and consequence manipulations may promote mand variability, extinction served as a viable option for increasing response variability. In this condition, they reinforced the first response of each complete mand frame, but put subsequent responses of that mand frame on extinction for the remainder of the phase.…”
Section: Responding Variably Under the Context Of Requestingmentioning
confidence: 99%
“…Based on the effectiveness of the multiple script training intervention used by Betz et al, Sellers (2011) asked whether or not teaching multiple scripts simultaneously would produce more reliable and faster acquisition of mand variability than teaching the scripts sequentially as was done in Betz et al (2011). Instead of teaching each participant to respond to a single auditory script at a time, Sellers used multiple script training to teach the participant to respond to textual scripts (typed scripts presented on pieces of paper).…”
Section: Responding Variably Under the Context Of Requestingmentioning
confidence: 99%
See 3 more Smart Citations